2014
DOI: 10.25100/cm.v45i2.1477
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine modifies blood glucose availability during prolonged low-intensity exercise in individuals with type-2 diabetes

Abstract: Objective: The study investigated the effect of supplementation with maltodextrin (CHO) alone or associated to caffeine during exercise in T2DM subjects. Methods: Pilot study, using Eight subjects with T2DM, aged 55±10 years, received CHO (1g/kg) or caffeine (1.5 mg/kg) alone or associated before exercise protocol. The exercise was executed at 40% heart rate (HR) reserve for 40 min, with 10-min recovery. Blood pressure (BP) and perceived exertion scale (Borg) were checked every 2 min. Blood glucose (BG) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Da Silva et al have studied the influence of 1.5 mg/kg caffeine intake on blood glucose levels in T2DM individuals throughout the exercise. This dose showed to be efficient for glucose-intolerance management [ 88 ]. Olivieri and Tipton have shown that 0.1–10 mM caffeine can inhibit SSAO activity IC 50 = 0.8 ± 0.3 mM in bovine serum [ 79 ].…”
Section: Promising Agents Involved In Regulating Semicarbazide-senmentioning
confidence: 99%
“…Da Silva et al have studied the influence of 1.5 mg/kg caffeine intake on blood glucose levels in T2DM individuals throughout the exercise. This dose showed to be efficient for glucose-intolerance management [ 88 ]. Olivieri and Tipton have shown that 0.1–10 mM caffeine can inhibit SSAO activity IC 50 = 0.8 ± 0.3 mM in bovine serum [ 79 ].…”
Section: Promising Agents Involved In Regulating Semicarbazide-senmentioning
confidence: 99%
“…Epidemiological studies showed that drinking coffee has positive effects on both glucose tolerance and sensitivity to insulin, thus reducing the risk of T2D over long periods of consumption [ 14 , 15 ]. Another study indicated that caffeine induced a significant reduction in blood sugar (about 65%) in T2D individuals during prolonged low-intensity exercise [ 16 ]. In addition, caffeine has shown to stimulate the intestinal anion secretion signalling pathway [ 17 ], resulting in membrane depolarisation and reducing the transmembrane Na + force responsible for the Na-dependent uptake of glucose [ 18 ].…”
Section: Introductionmentioning
confidence: 99%